Upaya Penanganan TB Paru pada Anak Perempuan Usia 1 Tahun di Puskesmas Babah Buloh Tahun 2025 - Farah Agustari; Hendra Wahyuni (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Tuberculosis (TB) is a chronic, infectious disease caused by the bacterium Mycobacterium tuberculosis. Primary infection occurs upon first exposure to bacillary tuberculosis, which often occurs in childhood, hence the term "childhood TB." The diagnosis of TB is usually made through a history that includes complaints of persistent cough, weight loss, fever, and weakness, along with a chest X-ray that shows typical abnormalities of pulmonary TB. In this case, a 21-month-old girl presented with a worsening, persistent cough accompanied by weight loss. The patient’s mother reported that her child frequently had fevers and appeared weak. After a physical examination and supporting tests, the patient was diagnosed with TB. The patient was given pharmacological therapy in the form of anti-tuberculosis drugs (OAT), and parents were educated about the importance of adherence to TB treatment as prescribed by the doctor. Furthermore, providing a balanced, nutritious diet is recommended to support successful treatment.